2007
DOI: 10.1074/jbc.m705811200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel CpG-free Vertebrate Insulator Silences the Testis-specific SP-10 Gene in Somatic Tissues

Abstract: Regulation of cell type-specific gene transcription is central to cellular differentiation and development. During spermatogenesis, a number of testis-specific genes are expressed in a precise spatiotemporal order. How these genes remain silent in the somatic tissues is not well understood. Our previous studies using the round spermatid-specific mouse SP-10 gene, which codes for an acrosomal protein, revealed that its proximal promoter acts as an insulator and prevents expression in the somatic tissues. Here w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(87 citation statements)
references
References 45 publications
4
83
0
Order By: Relevance
“…35 In addition, the C-terminal domain functions in the transcriptional repression of the mouse testis-specific SP-10 gene, regulating the tissuespecific expression of this gene. 36 Finally, the glycine-rich C-terminal domain binds several heterogeneous nuclear ribonucleoproteins involved in the biogenesis of mRNA. 37,38 Thus, while the physiological functions of TDP-43 are as yet incompletely characterized, TDP-43, and in particular the C-terminal domain, appears to function in the regulation of gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…35 In addition, the C-terminal domain functions in the transcriptional repression of the mouse testis-specific SP-10 gene, regulating the tissuespecific expression of this gene. 36 Finally, the glycine-rich C-terminal domain binds several heterogeneous nuclear ribonucleoproteins involved in the biogenesis of mRNA. 37,38 Thus, while the physiological functions of TDP-43 are as yet incompletely characterized, TDP-43, and in particular the C-terminal domain, appears to function in the regulation of gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…31,33,34 Instead, the C-terminus of TDP-43 is required for it to function as a suppressor at several splicing targets 35,36 and for TDP-43 to act as a transcriptional insulator for the mouse sp-10 gene. 37 Importantly, all but one of the ALS associated mutations in TDP-43 occur in the C-terminal domain.…”
Section: Evidence For Prion-related Q/n Domains In Tdp-43 and Fusmentioning
confidence: 99%
“…A recent report has shown that TDP-43, acting as a transcriptional insulator at the promoter of the spermatid-specific SP-10 gene, is predominantly present in the nuclear matrix fraction (Abhyankar et al, 2007). We wanted to test whether removal of TDP-43 disrupted chromatin organization.…”
Section: Chromatin Distribution Of the Rrm-1 Mutantsmentioning
confidence: 99%
“…hnRNP A1 and hnRNP A2/B1) through this region specifically. The functional importance of this domain in additional biological properties is highlighted by studies on the regulation of the spermatid-specific SP-10 gene (also known as ACRV1) (Abhyankar et al, 2007). Transcriptional inhibition of SP-10 by TDP-43 depends on the presence of the carboxyl domain and RRM-1 of the protein.…”
Section: Introductionmentioning
confidence: 99%